2019
DOI: 10.1111/ajd.12992
|View full text |Cite
|
Sign up to set email alerts
|

The use of cinacalcet for the treatment of calciphylaxis in patients with chronic kidney disease: A comprehensive review

Abstract: Calciphylaxis is a rare but life-threatening condition, most commonly affecting patients with stage 4 or 5 chronic kidney disease. No universally accepted therapy exists so far. In an attempt to avoid surgical intervention with parathyroidectomy, which is of questionable efficacy and carries several risks, a number of noninvasive treatments have been trialled with variable success. These treatments are aimed at modifying risk factors for calciphylaxis, in particular hypercalcaemia, hyperphosphataemia and hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The increased use of cinacalcet at baseline (19%) in the UKCS cohort may therefore represent underlying SHPT rather than a causative association. Deen et al have suggested the beneficial effects of cinacalcet as a treatment for CUA in a recent review [ 26 ]. The EVOLVE study also suggested that patients receiving cinacalcet for SHPT were less likely to develop calciphylaxis; 18 patients assigned to placebo developed calciphylaxis versus six assigned to cinacalcet [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased use of cinacalcet at baseline (19%) in the UKCS cohort may therefore represent underlying SHPT rather than a causative association. Deen et al have suggested the beneficial effects of cinacalcet as a treatment for CUA in a recent review [ 26 ]. The EVOLVE study also suggested that patients receiving cinacalcet for SHPT were less likely to develop calciphylaxis; 18 patients assigned to placebo developed calciphylaxis versus six assigned to cinacalcet [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive calcium and phosphate would deposit in the vascular wall, making the medial membrane and soft tissues prone to calcification that may aggravate or induce calciphylaxis [24,25]. Therefore, cinacalcet, which could improve bone markers and stabilize vascular calcification, may be preferable to PTX for calciphylaxis patients with SHPT, and PTX is reserved for refractory cases [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…3c and Supplementary Fig. 5), a treatment for secondary hyperparathyroidism 23 . Given aromatic conjugated ketones being challenged substrates for IREDs 20,24 , we applied kinetic resolution to synthesize bulky N-alkylated benzylamines.…”
Section: Resultsmentioning
confidence: 99%